Positioning Of Legal Philosophy To Maintain The Dignity Of Law Enforcement - Boy Nurdin; Juristo Juristo; Wahyu Widodo; Apriaji Setyawan; Ubaidilah Ishaq; Satria Dwi Rahardja; Anwar Sunarjo (Edunity Kajian Ilmu Sosial dan Pendidikan, 2024)
The enforcement of law is an integral aspect of the legal system's functioning, and it is often criticized with phrases like "no viral, no justice" or "law is sharp downwards, blunt upwards." In this context, how does the philosophy of law play a role in upholding the integrity of law enforcement, and how can a legal enforcement system be grounded in the rationality of legal philosophy. This type of research is normative with a conceptual approach based on secondary data. Secondary data is obtained through literature review and then analyzed qualitatively. Based on the analysis, it is found that the role of legal philosophy in maintaining the integrity of law enforcement involves guiding law enforcers to work effectively, respect, follow, and consistently apply rules to create balanced relationships by providing rights to everyone through fair and proportional procedures. A legal enforcement system based on the rationality of legal philosophy would involve:  Methodical Enforcement: Law enforcement. is conducted in a structured and systematic manner. Systematic Enforcement: Law enforcement follows a structured process. Coherent Enforcement: Law enforcement is logically consistent. Rational Enforcement: Law enforcement is based on reason rather than emotion. Comprehensive Enforcement: Law enforcement addresses all relevant aspects comprehensively. Radical Enforcement: Law enforcement applies thoroughly and decisively. Universal Enforcement: Law enforcement is applied universally, ensuring that it is fair and equal for all. This research confirms that a strong and integrated legal philosophy position in the law enforcement system is the key to maintaining and enhancing the dignity of the law itself. This requires commitment from all legal stakeholders to continue to apply and develop the principles of legal philosophy in every aspect of law enforcement.